2003
DOI: 10.1001/jama.289.13.1645
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Hydroxyurea on Mortality and Morbidity in Adult Sickle Cell Anemia

Abstract: CUTE CHEST SYNDROME AND painful episodes are the most common precedents of death in adults with sickle cell anemia (SCA). 1 A randomized, doubleblinded, placebo-controlled trial, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
512
5
29

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 806 publications
(568 citation statements)
references
References 34 publications
22
512
5
29
Order By: Relevance
“…Despite the lack of evidence that hydroxyurea therapy prevents organ damage, four large longitudinal studies have consistently demonstrated a survival advantage for children and adults on hydroxyurea therapy, when compared with their counterparts not on therapy. Long-term followup from the MSH study that included only adults with severe SCA demonstrated sustained clinical efficacy and 40% lower mortality after 9 years of follow up in participants electing to take hydroxyurea therapy after completion of the trial when compared with those not electing to start hydroxyurea therapy after completing the trial [57]. This survival benefit was maintained at 17.5 years [58].…”
Section: Hydroxyurea Therapymentioning
confidence: 89%
“…Despite the lack of evidence that hydroxyurea therapy prevents organ damage, four large longitudinal studies have consistently demonstrated a survival advantage for children and adults on hydroxyurea therapy, when compared with their counterparts not on therapy. Long-term followup from the MSH study that included only adults with severe SCA demonstrated sustained clinical efficacy and 40% lower mortality after 9 years of follow up in participants electing to take hydroxyurea therapy after completion of the trial when compared with those not electing to start hydroxyurea therapy after completing the trial [57]. This survival benefit was maintained at 17.5 years [58].…”
Section: Hydroxyurea Therapymentioning
confidence: 89%
“…Based on recent data demonstrating improved survival with hydroxyurea use, including patients with milder SCD phenotypes, we recommended hydroxyurea use for all adults without contra-indications or receiving chronic transfusions [17,18]. For those with a high rate of acute care utilization despite hydroxyurea therapy, we recommended a trial of prophylactic transfusions after careful consideration of risks of iron overload and alloimmunization [19].…”
Section: Discussionmentioning
confidence: 99%
“…Among chemotherapy agents, Hydroxyurea (HU) is commonly used as an anti-cancer agent [4]. For instance, HU is an effective reagent which was widely applied for treatment of acute angina, breast cancer, several hematological malignancies including chronic myelogenous leukemia (CML), sickle cell anemia, myeloproliferative disorders, and other known cancers previously [5][6][7][8][9]. In addition to its beneficial properties several disadvantages and side effects such as skin disorders were reported to be associated HU in consumers [10,11].…”
Section: Introductionmentioning
confidence: 99%